2019
DOI: 10.1021/acs.orglett.9b01869
|View full text |Cite
|
Sign up to set email alerts
|

Cycloisomerization of Conjugated Allenones into Furans under Mild Conditions Catalyzed by Ligandless Au Nanoparticles

Abstract: Au nanoparticles supported on TiO 2 (1 mol %) catalyze the quantitative cycloisomerization of conjugated allenones into furans under very mild conditions. The reaction rate is accelerated by adding acetic acid (1 equiv), but the acid does not participate in the protodeauration step as in the corresponding Au(III)-catalyzed transformation. The process is purely heterogeneous, allowing thus the recycling and reuse of the catalyst effectively in several runs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Our latest report, regarding the smooth Au/TiO 2 ‐catalyzed cycloisomerization of conjugated allenones into furans, urged us to examine the possible Au‐catalyzed cyclization of N ‐propargylic β‐enaminones ( N ‐1,5‐enynes), compounds that could be formally obtained from an uncatalyzed reaction between allenones and propargylamine . Indeed, propargylamine adds quantitatively to the model allenone 1 in dioxane as solvent within 10 min at 25 °C, yielding exclusively the (Z)‐enaminone 1′ .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our latest report, regarding the smooth Au/TiO 2 ‐catalyzed cycloisomerization of conjugated allenones into furans, urged us to examine the possible Au‐catalyzed cyclization of N ‐propargylic β‐enaminones ( N ‐1,5‐enynes), compounds that could be formally obtained from an uncatalyzed reaction between allenones and propargylamine . Indeed, propargylamine adds quantitatively to the model allenone 1 in dioxane as solvent within 10 min at 25 °C, yielding exclusively the (Z)‐enaminone 1′ .…”
Section: Methodsmentioning
confidence: 99%
“…of propargylamine in toluene at 25 °C for 10 min, and then adding the catalyst followed by heating, resulted to the same outcome, as in the case of using directly 1′ . In fact, premixing the reactants for 10 min is more than enough, otherwise unreacted allenone 1 should had been instantaneously isomerized by Au/TiO 2 into 2‐( p ‐tolyl)furan . The catalytic system (Au/TiO 2 ) is recyclable by simple filtration, washing and drying at 90 °C for 2 h. It was reused in five consecutive runs with little loss of activity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the additives (such as small molecule bases or acids) also have some significant impacts on the synthesis of furans. Zorba et al declared that HOAc was found as an appropriate additive to effectively promote the cycloisomerization of conjugated allenones into furans under mild conditions catalyzed by ligandless Au‐nanoparticles in yield of 99% . A simple and convenient approach for the construction of 2‐acetyl trisubstituted furans with acetylenic ketones and 1,3‐dicarbonyl compounds via the Cu‐mediated unstrained C (sp 3 )‐C (sp 2 ) bond cleavage has been described by Fan and coworkers, and the furans were isolated with a yield up to 67% when 0.2 equiv.…”
Section: Introductionmentioning
confidence: 99%